Analisis Availability Metrics Webserver Penyedia Website Program Studi Teknik Elektro Fakultas Teknik Universitas Udayana - Pratama, Dwi Yoga; Sukadarmika, Gede; Putra Sastra, Nyoman (Jurnal SPEKTRUM; Vol 6 No 3 (2019): Jurnal SPEKTRUMDO - 10.24843/SPEKTRUM.2019.v06.i03.p05, 2019)
This research aims to observe and find out the availability value of the system that provides website access of the Electrical Engineering Study Program at the Faculty of Engineering, Udayana University. To find the availability values, data collection was carried out on each network devices by using a network monitoring program called CACTI based on Simple Network Management Protocol. The data were in the form of PING Latency from each network devices consisting of one server, two switches, and two routers. From the PING Latency data, then the value of Mean Time to Failure and Mean Time to Recover can be calculated which is used to determine the availability value of the network device. After all network devices had the availability values, then a calculation was made to determine the availability value of the entire website service provider system of the Electrical Engineering Study Program, Faculty of Engineering, Udayana University which from the result of this research found that Electrical Enginering’s Website has availability values of 99.9%.